Association of Estimated Insulin Resistance with N-Terminal B-Type Natriuretic Peptide Concentration in Men with Metabolic Syndrome. (18th December 2019) - Krzesiński, Paweł; Piechota, Wiesław; Piotrowicz, Katarzyna; Gielerak, Grzegorz; Woźniak-Kosek, Agnieszka
Abstract : Background . The diagnostic and prognostic role of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in heart failure is well established. However, additional factors may influence its concentration. One of them is obesity, which in general is accompanied by reduced NT-proBNP levels. However, specific data concerning metabolic syndrome (MS) are equivocal. The aim of the present study was to evaluate the association of NT-proBNP with estimated insulin resistance (eIR) in men with MS. Methods . In 86 male patients with MS (78 of them hypertensive), blood pressure, anthropometric measures, NT-proBNP, creatinine, glucose, and insulin were assessed and eIR was calculated using homeostatic model assessment (HOMA-IR). Results . Both eIR and age were independently associated with NT-proBNP concentrations ( b  = 0.2248, p = 0.019 ; b  = 0.0102, p = 0.049, respectively). Blood pressure, anthropometric measures, and eGFR were not correlated with NT-proBNP. Patients without eIR had higher NT-proBNP than those with eIR (32.2 ± 26.4 vs 21.4 ± 25.4 pg/mL, p = 0.014 ). The difference was even higher in the younger subgroup of patients reaching nearly 50%. Conclusions . Insulin resistance and, to a lesser degree, age were associated with NT-proBNP levels in men with MS. In younger subjects with eIR, mean NT-proBNP level was lower than in corresponding healthy age males.